Hypoadrenocorticism in dogs - the Mad Hatter of veterinary internal medicine - Palić, Magdalena (Array, 2020)
Hypoadrenocorticism arises from insufficient adrenal gland function and is also known as Addison’s disease, a rarely occurring disease (0.1%) in dogs. Due to its oscillatory course and overall nonspecific symptoms, it is a diagnostic challenge for clinicians, and is often misdiagnosed or unattended among other differentials. There are two forms of hypoadrenocorticism: primary and secondary. The aim of this study was to analyse the data of dogs suffering from Addison’s disease, treated at the Clinic for Internal Medicine, Faculty of Veterinary Medicine, University of Zagreb, Croatia and to compare them with data from similar institutions worldwide. The archive of Clinic for Internal Medicine, Faculty of Veterinary Medicine, Zagreb, Croatia was searched to investigate and statistically analyse signalment, clinical and laboratory data, and the duration of symptoms, treatment protocols and outcome of canine hypoadrenocorticism. The study group included 14 dogs (36% male and 64% female) diagnosed with hypoadrenocorticism. All dogs had a history of gastrointestinal symptoms, i.e. vomiting in 100%, diarrhoea in 64% and melena in 7%. Hypovolemic shock was noted in 57%, hypothermia in 64% and bradycardia in 29% of cases. The most frequently observed laboratory abnormalities were an increase in BUN (86%), creatinine (57%) and potassium concentration (79%), and a decrease in sodium (71%), Na/K ratio (86%), cholesterol (21%) and glucose concentration (21%). Duration of symptoms (till ACTH stimulation test performance) was broad, from 2 – 2190 days (median 90±1195.5 days). The outcome was favourable in 100% cases after initiation of adequate treatment.